SUBJECTIVE WELL-BEING SISWA MAN 3 PALEMBANG YANG TINGGAL DI ASRAMA - Fara Hamdana; Alhamdu Alhamdu (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2015)
The purpose of this study want to examine the subjective well-being condition of students MAN 3 Palembang that stay in dormitory, and also want to find the factors that influences subjective well-being condition of students. The samples of this study chosen by cluster sampling and survey quantitatif approach used in this study.The result found that subjective well-being condition of students MAN 3 Palembang that stay in dormitory there are in moderate position with values 71,2% or 74 students. Then, this study also found three factors that influences positive and negative subjective well-being condition. Three factors that influences positive well-being condition there are; enjoyable friends, be autonomous, and self-discipline. In others hand, three factors that effect negative subjective well-being condition there are; less facilities of dormitory, solid and monotonous activities, and petulantly supervisor.